The effect of anthropogenic noise as a source of acoustic stress in wild populations of Hippocampus guttulatus in the Ria Formosa - Magalhães, Marisa Raquel Gonçalves (2017)
Dissertação de mestrado, Biologia Marinha, Faculdade de Ciências e Tecnologia, Universidade do Algarve, 2016